2016
DOI: 10.1016/j.cdtm.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes awareness, treatment, control rates and associated risk factors among Beijing residents in 2011: A cross‐sectional survey

Abstract: ObjectiveTo examine the awareness, treatment and control rates of diabetes and identify their associated risk factors among Beijing residents.MethodsA cross-sectional survey was conducted in 2011, using a stratified multistage cluster random sampling method to select a representative sample of 20,242 residents in Beijing aged 18–79 years. Diabetes was defined as fasting blood glucose (FBG) ≥7.0 mmol/L and/or history of diabetes and/or using insulin or hypoglycemic agents. All estimates of awareness, treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
2
7
1
2
Order By: Relevance
“…The percentage of those receiving care for DM was still lower than that reported for Malaysia (87.5%) [33] and Portugal (79.7%) [9] but higher than those for Kazakhstan (65.6%) [25], southern cone of Latin America (58.8%) [34], China (48.1%) [22], and Bangladesh (36.9%) [32]. Based on the results of this and other studies, receiving treatment was highly associated with obesity in patients with DM [35].…”
Section: Discussionmentioning
confidence: 75%
“…The percentage of those receiving care for DM was still lower than that reported for Malaysia (87.5%) [33] and Portugal (79.7%) [9] but higher than those for Kazakhstan (65.6%) [25], southern cone of Latin America (58.8%) [34], China (48.1%) [22], and Bangladesh (36.9%) [32]. Based on the results of this and other studies, receiving treatment was highly associated with obesity in patients with DM [35].…”
Section: Discussionmentioning
confidence: 75%
“…In 2011, the rates of treatment and control of diabetes in urban China were 51.3 and 33.8%, according to a survey with 20,242 residents aged 18-79 years old [15]. A cross-sectional survey conducted in Northeast China indicated that the treatment and control rates of diabetes mellitus were 52.9 and 44.2% in 2012 for participants aged 18 to 79 years old [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous regional surveys had been conducted to investigate the prevalence, treatment, and control of diabetes in China [12][13][14][15][16]. However, few of these studies were focused on the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with both hypertension and T2DM, 90% of them reported having received T2DM treatment, which was much higher than two previous studies conducted in Portugal (79.7%) and China (51.3%) among T2DM patients [27,28]. The disparity may be mainly due to different subjects and de nitions of T2DM treatment.…”
Section: Discussionmentioning
confidence: 67%